First forecast of a sudden stratospheric warming with a coupled whole‐atmosphere/ionosphere model IDEA. Issue 3 (28th March 2014) - Wang, H.; Akmaev, R. A.; Fang, T.‐W.; Fuller‐Rowell, T. J.; Wu, F.; Maruyama, N.; Iredell, M. D.
Abstract We present the first "weather forecast" with a coupled whole‐atmosphere/ionosphere model of Integrated Dynamics in Earth's Atmosphere (IDEA) for the January 2009 Sudden Stratospheric Warming (SSW). IDEA consists of the Whole Atmosphere Model and Global Ionosphere‐Plasmasphere model. A 30 day forecast is performed using the IDEA model initialized at 0000 UT on 13 January 2009, 10 days prior to the peak of the SSW. IDEA successfully predicts both the time and amplitude of the peak warming in the polar cap. This is about 2 days earlier than the National Centers for Environmental Prediction operational Global Forecast System terrestrial weather model forecast. The forecast of the semidiurnal, westward propagating, zonal wave number 2 (SW2) tide in zonal wind also shows an increase in the amplitude and a phase shift to earlier hours in the equatorial dynamo region during and after the peak warming, before recovering to their prior values about 15 days later. The SW2 amplitude and phase changes are shown to be likely due to the stratospheric ozone and/or circulation changes. The daytime upward plasma drift and total electron content in the equatorial American sector show a clear shift to earlier hours and enhancement during and after the peak warming, before returning to their prior conditions. These ionospheric responses compare well with other observational studies. Therefore, the predicted ionospheric response to the January 2009 SSW can be largely explained in simple terms of the amplitude and phase changes of the SW2 zonal wind in the equatorial E region.